2022
DOI: 10.3390/ijms23169165
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Alterations Induced by Two Ecologically Relevant Concentrations of Lead on Danio rerio Gills

Abstract: Lead (Pb), due to its high toxicity and bioaccumulation tendency, is one of the top three pollutants of concern for both humans and wildlife and occupies second place in the Priority List of Hazardous Substances. In freshwater fish, Pb is mainly absorbed through the gills, where the greatest accumulation occurs. Despite the crucial role of gills in several physiological functions such as gas exchange, water balance, and osmoregulation, no studies evaluated the effects of environmentally relevant concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The analytical verification of the actual concentrations was performed throughout the experiment (starting from time 0 every 24 h) (Table S1). No evident variation was recorded, and such a result is in agreement with the data from previous studies ( [25] and the references therein).…”
Section: Exposure Conditionssupporting
confidence: 93%
See 2 more Smart Citations
“…The analytical verification of the actual concentrations was performed throughout the experiment (starting from time 0 every 24 h) (Table S1). No evident variation was recorded, and such a result is in agreement with the data from previous studies ( [25] and the references therein).…”
Section: Exposure Conditionssupporting
confidence: 93%
“…An increase in MT expression has been demonstrated in the liver of both marine and freshwater fish after dietary exposure to Pb, and in fish coming from Pb-contaminated areas [49,79]. Furthermore, our recent study reported an increase in the expression of mtf1 in zebrafish gills after Pb exposure [25]. Although MT induction has been demonstrated in several fish organs after exposure to heavy metals, the liver is one of the organs that first responds to the toxic input [79].…”
Section: Gene Expressionmentioning
confidence: 92%
See 1 more Smart Citation
“…Huang et al (2014) reported that Pb may be present in a high concentration in storm water runoff ranging from 75 to 926 ppm. According to Curcio et al (2022), Pb is present in water bodies within the range of 0.05 to 566.2 ppm. Hence the selected dose (43.3 ppm of Pb) used in the present study may be considered as environmentally relevant.…”
Section: Methodsmentioning
confidence: 99%
“…Being exposed directly to external environments, the gill is one of the primary organs for osmoregulation in fish and is sensitive to physical and chemical changes in aquatic environments such as temperature, acidification of water supplies, salts and heavy metals and water borne toxicants [14,15]. The gill has several functions, including gas exchange and osmoregulation [16,17]. It has been claimed that fish osmoregulation requires a substantial amount of metabolic energy [18,19].…”
Section: Introductionmentioning
confidence: 99%